Exploring Indonesian Panic Buyers’ Typologies in Time of Covid-19 Pandemic - Lukitaningsih, Ambar; Hartono, Arif (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
Purpose – This study aims to investigate hitherto unresearched panic buyer (shopper) typologies among Indonesian consumers as a result of the COVID-19 outbreak. In this study, a panic buyer (shopper) is described as a customer who worries about their stock during a pandemic and decides to purchase things in bulk or in greater quantities at the start of the pandemic. Design/methodology/approach – To identify probable groupings of the items, an exploratory factor analysis is carried out using principal component analysis and varimax rotation. Then to identify consumer groups, a two-step cluster analysis was conducted. Lastly, an ANOVA test is run on the whole set of variables to identify differences between the detected clusters in order to validate the cluster solutions. Findings – Five components that served as the foundation for the typology emerged from exploratory factor analysis. Using behaviour and attitude factors including